Empowering sickle cell disease care: the rise of TechnoRehabLab in Sub-Saharan Africa for enhanced patient's perspectives - Boma, Paul Muteb; Ngoy, Suzanne Kamin Kisula; Panda, Jules Mulefu; Bonnechère, Bruno (Frontiers in Rehabilitation Sciences, 2024)
Sickle-cell Disease (SCD) is a major public health problem in Africa, and there are significant obstacles to its comprehensive management, particularly in terms of access to appropriate healthcare. This calls for inventive approaches to improve patients' prospects. Among the major challenges to be met are the primary and secondary prevention of certain serious complications associated with the disease, such as neurocognitive, motor and respiratory functional disorders. This perspective argues for the rapid creation of specific, cost-effective, technology-supported rehabilitation centres to advance SCD care, identify patients at high risk of stroke and implement tailored rehabilitation strategies. The TechnoRehabLab in Lubumbashi illustrates this shift in thinking by using cutting-edge technologies such as virtual reality (VR), serious games and mobile health to create a comprehensive and easily accessible rehabilitation framework. Diagnostic tools used to perform functional assessment can be used to identify cognitive, balance and walking deficits respectively. Transcranial Doppler enables early detection of sickle cell cerebral vasculopathy, making it possible to provide early and appropriate treatment. VR technology and serious games enable effective rehabilitation and cognitive stimulation, which is particularly advantageous for remote or community-based rehabilitation. In the context of African countries where there is a glaring disparity in access to digital resources, the TechnoRehabLab serves as a tangible example, demonstrating the flexibility and accessibility of technology-assisted rehabilitation. This perspective is an urgent call to governments, non-governmental organisations and the international community to allocate resources to the replication and expansion of similar facilities across Africa.